Combined treatment of postmenopausal patients with pelvic organ prolapse and genitourinary syndrome - Yulia E. Dobrokhotova; Irina A. Lapina; Anatoly G. Tyan; Vladislav V. Taranov; Tatiana G. Chirvon; Nikita V. Glebov; Olesya V. Kaykova; Anastasiya A. Malakhova; Valeriia M. Gomzikova; Ekaterina S. Mahonina; Mariya A. Olkhovskaya (IP Berlin A.V., 2024)
Background. Colpoptosis combined with stress urinary incontinence is one of the most common conditions in postmenopausal women. Menopause is also associated with the risk of genitourinary syndrome due to estrogen deficiency. Despite the variety of options for surgical correction of genital prolapse and urinary incontinence, there is no universal technique. The use of vaginal approach in pelvic floor surgery is associated with several controversies regarding the rates of recurrence and mesh-associated complications. Studies of the state of the endothelium in menopause have demonstrated a close relationship between age-related features and the frequency of adverse clinical outcomes, which requires an optimal intervention not only on the hormonal status but also on the microcirculatory system. Aim. To improve the principles of complex treatment of pelvic organ prolapse and genitourinary syndrome in postmenopausal patients. Materials and methods. The study included 48 postmenopausal patients with genital prolapse of stage II and above according to the POP-Q classification. All patients received continuous menopausal hormone therapy (MHT) with a combined estrogen-progestogen agent. The patients in group 1 (n=24) received MHT according to clinical guidelines for managing patients with genitourinary syndrome. The patients in group 2 (n=24), in addition to MHT, received sulodexide containing glucurono-2-amino-2-deoxyglucoglucan sulfate before the intended surgical treatment and for 30 days after surgery. Correction of colpocystocele, proctocele and stress urinary incontinence was performed using anterior and posterior colporrhaphy, perineoplasty, and urethral sling placement in case of stress urinary incontinence. Results. Six months after surgical treatment, signs of genital prolapse recurrence were detected in 3 patients (12.5%) in group 1, and 1 patient (4.2%) showed signs of mesh-associated complications (implant extrusion) after urethral sling placement. In group 2, only 4.2% of patients (n=1) showed signs of recurrence of stage II cystocele. All patients who underwent urethral sling surgery reported improved urinary incontinence (n=10). During complex therapy, 3 months after surgery, a more significant improvement of endothelial dysfunction markers was noted in group 2 patients (homocysteine level in group 1 after treatment was 12.27±0.34, in group 2 - 8.34±0.24). Conclusions. Combination therapy of genitourinary syndrome and genital prolapse using MHT, endotheliotropic drugs and vaginal surgical approach in postmenopausal patients contributes to effective and safe treatment associated with minimal risk of complications and recurrence rate. Endothelial dysfunction correction is an essential step in planning surgical intervention in menopausal patients, which contributes to improving tissue repair in the postoperative period.